Achieving cultural resonance: Four strategies toward rallying support for entrepreneurial endeavors - Soublière, Jean‐François; Lockwood, Christi (Strategic Management Journal, 2022)
Abstract Research Summary We theorize the strategies that entrepreneurial actors employ to instill their endeavors with culturally resonant meanings and rally the support of key audiences (investors, analysts, or customers). In extant cultural entrepreneurship research, endeavors are assumed to achieve resonance and gain support when actors deploy the culture they share with their targeted audiences. But what if actors and audiences hold cultural repertoires that poorly overlap? We consider actors' efforts to “mobilize” and “enrich” the repertoires of both parties. Specifically, we introduce a typology identifying four strategies: anchoring, retooling, channeling, and seeding. Viewing culture as an engine of stability and change, we contend that each strategy addresses a distinct tension that actors must skillfully balance. We develop propositions to explain how and when actors manage these tensions. Managerial Summary Entrepreneurs must explain their endeavors in terms that audiences (investors, analysts, or customers) will understand and value. We know that entrepreneurs do so by telling stories and performing other symbolic actions, or by revising their stories and actions. However, prior insights assume a preexisting fit between what entrepreneurs and audiences value. How is this fit created? We identify four strategies by which entrepreneurs leverage a preexisting fit, and foster greater fit. We explain how entrepreneurs leverage a preexisting fit by presenting endeavors in familiar terms, and guiding audiences' interpretations. We explain how entrepreneurs foster greater fit by learning what audiences value, and educating audiences about their endeavors' value. Considering the inherent tension that each strategy entails, we explain how and when entrepreneurs use these strategies.